ADM FORMALISM FOR SCALAR PERTURBATION IN THE COSMIC INFLATION EPOCH - PEBRALIA (NIM : 20214001), JESI
This theses discussed about scalar perturbation in the cosmic inflation epoch. The equation of motion of scalar perturbation derived from the action of scalar curvature of StarobinskyÃ‚Â’s model using Arnowitt-Desser-Misner (ADM) formalism. The action of scalar perturbation expanded until second order in term of curvature perturbation variable. The result of this formalism is use to describe the equation of motion and two-point correlation function of scalar perturbation in the cosmic inflation epoch.